Measurement Straight Leg Raise for Low Back Pain Based Grayscale Depth - Tavipia Rumambi; Hustinawaty Hustinawaty; Sarifuddin Madenda; Eri Prasetyo Wibowo (Universitas Ahmad Dahlan, 2017)
Spinal disorders are the most frequent cause of pain and lower part of the spine, which is often called Low Back Pain.Straight Leg Raise Test can provide important information to detect the cause of LBP. Straight Leg Raise test conducted by physican with a goniometer required accurately reading angle when your feet up. But this can be overcome with Kinect can detect motion and displays images and depth data. Methodological includes image acquisition method using RGB and Grayscale depth, skeleton tracking, feature extraction detection Straight Leg Raise . The proposed algorithm describes a method for estimating the data triangulation angle Straight Leg Raise by Kinect. Results measurement if the positive Low Back Pain below 60 degrees there is a tendency to suffer from one of the causes of Low Back Pain. The results can be stored in the database as medical history and used to monitor the progress of therapy